From Financial Distress to Fraud: A Socio-Economic Analysis of Corporate Accountability Moderated by Audit Quality in Indonesia’s Mining Sector - Shelly Lusiana; Taufik Akbar (Universitas Pattimura, 2026)
This study examines the influence of financial distress and independent commissioners on financial statement fraud, with audit quality serving as a moderating variable, in mining companies listed on the Indonesia Stock Exchange between 2020 and 2024. Grounded in a socio-economic perspective, the research conceptualizes financial reporting fraud as a structural response to economic pressure and governance limitations rather than merely individual managerial misconduct. Using a quantitative causal research design, the study analyzes secondary data from 52 mining firms selected through purposive sampling. Financial distress is measured using the G-Score, financial statement fraud is proxied by the F-Score, and audit quality is classified based on Big Four and non–Big Four auditors. Data are analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings indicate that financial distress has a significant positive effect on financial statement fraud, while the proportion of independent commissioners does not exhibit a significant influence. Furthermore, audit quality does not moderate the relationship between financial distress and fraud, nor between independent commissioners and fraud. These results suggest that financial pressure remains the dominant driver of fraudulent reporting in Indonesia’s mining sector, whereas formal governance and external assurance mechanisms have yet to function effectively. This study contributes to the literature by integrating socio-economic and governance perspectives to explain financial statement fraud as a relational and structural phenomenon within emerging market contexts.